Personal Factors and Mental Health of Public School Teachers in Lavezares I District, Northern Samar, Philippines: A Recent Study - Alcera, Rona L.; Donoga , Danhill C.; Turla, Margaret A.; Balag , Cecil C. (Current Overview on Disease and Health Research Vol. 5, 2022)
The research focuses on the personal factors that influence public-school teachers' mental health. This survey was given to elementary and secondary school teachers in Lavezares I District, Division of Northern Samar. The descriptive-correlational research design was used in this study, which included 30 participants chosen through purposive sampling. Descriptive statistics and the Pearson Product-Moment Correlation Coefficient were used to analyse survey questionnaire data. This was done during the third quarter of the 2021-2022 school year. According to the findings, the majority of them are between the ages of 31 and 38. The majority of them are female, married, with a net take-home pay of 5,000 - 11,499, recipients of completed academic requirements (CAR) for their MA, hold a teacher III position, have been in the service for 7 years or less, and have attended no more than two distance learning trainings and seminars. In regards to mental health, outcomes revealed that teachers at the forefront of distance learning implementation experience severe stress, moderate anxiety, and mild depression. The demographic data of age, gender, civil status, net take-home pay, highest educational attainment, teaching position, length of service, and number of attended distance education trainings and seminars were found to be unrelated to teachers' mental health. The results of this research will provide insight into how schools can address personal factors and mental health issues of teachers in order for them to become resilient in the face of adversity.